Kopoliester butyrylo-acetylowy chityny jako nowy aktywny składnik nanokompozytów polimerowo-włóknistych - Draczyński, Zbigniew (Wydawnictwo Politechniki Łódzkiej, 2013)
W pracy przedstawiono nowe perspektywiczne źródło chityny – ciała pszczół miodnych. Opracowano metodykę pozyskiwania i oczyszczania chityny o dogodnych do dalszych prac parametrach fizykochemicznych. Wykazano, iż chityna pozyskiwana z tego źródła charakteryzuje się budową i właściwościami fizykochemicznymi zgodnymi z chityną handlową, pozyskiwaną z odpadów przemysłu spożywczego.

The paper presents a new perspective source of chitin – bodies of naturally dead honeybees. A method for obtaining and purification of chitin suitable for further work physicochemical parameters was developed. It has been shown that chitin obtained from this source has the structure and physicochemical properties compliant with commercial chitin extracted from the food industry. It has been shown possible to carry out the synthesis of a new polymer – ester derivative of chitin containing the two different pendant groups derived from butyric acid (butyryl groups) and acetic acid (acetyl groups). This derivative of chitin, which has good solubility in common organic solvents, is formed by esterification of chitin by a mixture of butyric acid anhydride and acetic acid anhydride. In the course of the work optimal synthesis conditions of the copolyester butyrylacetyl chitin (BAC) with established physical and chemical parameters was developed.
Keywords: organic solvents; derivative chitin; pochodne chityny; kopolimery; nanokompozyty